Pengaruh Keterlibatan (Involvement), Konsistensi (Consistency), Adaptasi (Adaptability) dan Misi (Mission) terhadap Kinerja Pegawai pada Kantor Pelayanan Kekayaan Negara dan Lelang Pematangsiantar - Ika Dany Sitepu (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the influence of involvement, consistency, adaptability, and mission on employee performance at the Pematangsiantar State Asset and Auction Service Office (KPKNL). The research method used a quantitative approach, with data collected through questionnaires distributed to all 34 permanent employees. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results showed that all independent variables—involvement, consistency, adaptability, and mission—had a positive and significant effect on employee performance, with the mission variable having the most dominant influence. An R-square value of 0.825 indicates that these four variables explained 82.5% of the variation in employee performance. The conclusion of this study is that involvement, consistency, adaptability, and mission are important factors that simultaneously play a strategic role in improving employee performance at the Pematangsiantar KPKNL.   Keywords: Adaptation, Employee Performance, Involvement, Consistency